Pamięć zbiorowa a indywidualne wizje przyszłości w filmie Kiriłła Sieriebriennikowa Uczeń - Raspapou, Aliaksandr (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article discusses the functioning of collective memory and its manifestations in contemporary Russian cinematography. The author analyzes the play Martyr by the German playwright Marius von Mayenburg and compares it with the film The Student directed by a Russian filmmaker Kirill Serebrennikov. The author refers to the concept of collective memory in order to explain its significance in the process of constructing and preserving national identity. On the basis of this analysis it is shown that the youngest generation of Russians are experiencing an identity crisis, and that they are trying to redefine the models and patterns imposed on it in an effort to find its place in today’s world.